Eupatilin Exerts Antinociceptive and Chondroprotective Properties in a Rat Model of Osteoarthritis by Downregulating Oxidative Damage and Catabolic Activity in Chondrocytes - Jeong, Jeong-Hee; Moon, Su-Jin; Jhun, Joo-Yeon; Yang, Eun-Ji; Cho, Mi-La; Min, Jun-Ki (PLOS ONE, 2015)
Increases in oxidative stress are thought to be associated with the development of osteoarthritis (OA). Eupatilin, one of the major compounds present in artemisia species, was shown to have both anti-oxidative and anti-inflammatory properties. Here, we investigated the in vivo effects of eupatilin on pain severity and cartilage degradation in an experimental rat model of OA, along with the mechanisms of action underlying these effects. Experimental OA was induced via an intra-articular injection of monosodium iodoacetate (MIA), with oral administration of eupatilin initiated on the day of MIA injection. Pain was assessed by measuring the paw withdrawal latency and threshold. Cartilage destruction was analyzed macroscopically and histomorphologically. The effects of eupatilin on mRNA expression were investigated in interleukin-1β (IL-1β)-stimulated human OA chondrocytes. Eupatilin treatment exhibited clear antinociceptive effects, along with an attenuation of cartilage degradation in OA rats. Additionally, the number of osteoclasts present in the subchondral bone region was significantly decreased following eupatilin treatment. Eupatilin reduced the expression of interleukin-1β (IL-1β), interleukin-6 (IL-6), nitrotyrosine and inducible nitric oxide synthase (iNOS) in cartilage. mRNA levels of matrix metalloproteinase-3 (MMP-3), MMP13, and a disintegrin and metalloproteinase with thrombospondin motifs-5 (ADAMTS-5) were reduced in IL-1β-stimulated human OA chondrocytes, while tissue inhibitor of metalloproteinases-1 (TIMP-1) was induced. Phosphorylated protein levels of the c-jun N-terminal kinase (JNK) was reduced by eupatilin. Taken together, these results suggest that eupatilin suppresses oxidative damage and reciprocally enhances extracellular matrix production in articular chondrocytes, making eupatilin a promising therapeutic option for the treatment of OA.